Hubungan Stres dengan Tingkat Kecanduan Game Online pada Siswa SMPN 5 Padang - Estiayuning Tias; Rini Gusya Liza; Roni Eka Sahputra (Fakultas Kedokteran, Universitas Andalas, 2021)
Background. Stress is a mental health disorder that often occurs. Stress is due to physical and psychological imbalances in dealing with pressures in daily life. Adolescents are highly sensitive stage of human development in dealing with stress. Online game is popular among adolescents. Online game addiction is a gaming disorder due to excessive use of online games. Adolescents played online games as a way to relieve stress and increased the risk of addiction. Online game addiction in adolescents can impact on their behavior, academic performances, and may lead to physical illness. Objective. This study aims to examined the relationship between stress and online game addiction levels. Methods. This present research was done in Junior High School at 5 in Padang since October to November in 2019 with sixthy six samples of ninth of grade. This cross sectional research approach with stratified random sampling. The data collected that analyzed using chi-square test. Results. The research showed 50% subjects had no stress and 51,5% subjects had no online game addiction with the significant value was p=0,044 (p value < 0.05). Conclution. There were relationship between stress and online game addiction levels in student of Junior High School at 5 in Padang.